Perubahan Budaya dalam Ritual Slametan Kelahiran di Cirebon, Indonesia - Busro, Busro; Qodim, Husnul (Jurnal Studi Agama dan Masyarakat, 2018)
This study attempts to investigate the ritual practice of slametan birth in Kedungsana Village, Plumbon District, Cirebon Regency. The method used in this study is descriptive method. The data are collected through observation and interview techniques to ritualists, local leaders, religious leaders and others. The purpose of this study is to find out the procedures for practicing ritual of slametan birth, how the culture shifted in the ritual slametan birth, and the factors causing to cultural shift in ritual of slametan birth. The study reveals that ritual of slametan birth is still carried out by the community as a thanksgiving to Allah SWT for all the blessings that have been given and kept away from everything that is not desirable. Cultural shift occurred in the ritual practice of slametan birth. Factor that causes to cultural shifts in the ritual practice of slametan birth is the progress of thinking and technology. This factor only affects to some young age people relatively.